2016
DOI: 10.29407/jetar.v1i1.257
|View full text |Cite
|
Sign up to set email alerts
|

Edmodo Virtual Learning Environments in Teaching English

Abstract: AbtractIn recent years, the integration of Information and Communication Technology (ICT), especially the internet, in teaching and learning process becomes an essential part of the teachers’ duties. As a teacher, we should be able to integrate the internet in teaching and learning process and purpose of this new medium as potential source to our students to improve their English competence. One of the internet facilities is Edmodo. It refers to as with any social network, can be used as a place to post and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Learning English today may be more rewarding thanks to paid and free online learning resources. Aji, M. P. P. (2016) emphasized that as technology advances, teaching using multimedia and online courses have become a more popular way to teach English.…”
Section: Introductionmentioning
confidence: 99%
“…Learning English today may be more rewarding thanks to paid and free online learning resources. Aji, M. P. P. (2016) emphasized that as technology advances, teaching using multimedia and online courses have become a more popular way to teach English.…”
Section: Introductionmentioning
confidence: 99%
“…The result of the research showed that Edmodo can be integrated into GBA writing cycles. Additionally, Inayati, Asib, and Drajati (2019), Aji (2016), and Gay & Sofyan (2017) focused on investigating the role of Edmodo in the teaching and learning process. They found that learning platforms, especially Edmodo, successfully support and facilitate both teachers and students in the teaching and learning activities.…”
Section: Introductionmentioning
confidence: 99%